Detail Engineering Design of Compact Neutron Generator to Support BNCT Facility in Indonesia - Widarto Widarto (Indonesian Journal of Physics and Nuclear Applications, 2018)
Boron Neutron Capture Therapy (BNCT) is a method of cancer therapy based on neutron radiation which has advantages over the other cancer therapy methods. It uses a stable isotope of 10B which will be an excited isotope of 11B when irradiated by thermal neutron. It immediately (in 10-12 s) breaks into α particle and a lithium recoil nucleus. The two secondary particles play important roles in killing cancer cells. They have a short range in tissue (5 µm and 9 µm respectively) which is less than the average dimension of a cell. This leads to the damage of cancer cell only but the normal cells remain safe. Thermal and epithermal neutrons play important roles in BNCT. From the beginning the neutron sources for BNCT are nuclear reactors which produce high intensity of thermal neutrons (En <0.5 eV), epithermal neutrons (0.5 eV< En < 10 keV) and fast neutrons (En > 10 keV). However, nuclear reactors are very expensive and too large to be used in hospitals. In addition, the operation of nuclear reactors is under restricted protocols related to safety and physical protection. A compact neutron generator is a good choice of neutron source for BNCT. The advantages of compact neutron generator are that the size is small and that the neutron yield is more than 109 ns-1 which satisfies the requirement recommended by IAEA. Additionally, the neutron energy is not so high that it requires a complicated neutron collimator, the operation is easy, and the public acceptance is higher than with nuclear reactors. Based on the requirements of epithermal neutron beam for BNCT facility, the detailed engineering design of compact neutron generator has been made.